Effect of Process Parameter Variations in TIG Welding on Joint Strength - Ishaan, Rohan; Siddhartha, Aswin (Institute of Computer Science (IOCS), 2025)
This research investigates the effect of process parameter variations in Tungsten Inert Gas (TIG) welding on joint strength, focusing on the key parameters that influence weld quality and mechanical properties. The study explores the relationship between welding current, welding speed, arc length, shielding gas flow rate, and electrode type, and their impact on the tensile strength, fatigue resistance, and overall integrity of welded joints. Through a series of controlled experiments, various combinations of these parameters were tested to identify optimal settings for achieving the strongest, most reliable welds. The results indicate that welding current and speed have the most significant influence on joint strength, with proper shielding gas flow and arc length playing critical roles in minimizing defects and ensuring a stable weld pool. The research also highlights the importance of adjusting welding parameters based on material type and application to achieve maximum joint strength while improving efficiency and reducing material waste. The findings provide valuable insights for improving welding practices, optimizing process parameters, and enhancing the quality and durability of welded structures in industrial applications. This study contributes to the development of more effective welding procedures, offering practical solutions for industries relying on high-quality welds for structural integrity and safety.